The Correlation Between Sleep Duration And Learning Achievement Of Efl Students - Rizki Hasanah; Abdul Syahid; Ayu Sundari; Mayra Musdalifah; Kholida Ziya; Siti Rahmawati; Alya Audria (Gudang Jurnal Multidisiplin Ilmu, 2023)
This quantitative descriptive study aimed to explore the relationship between sleep duration and academic performance among third-year English Language Teaching students at IAIN Palangka Raya. data was collected from 24 voluntary participants. Results indicated that most respondents slept between 11:00 pm and 12:00 am, with an average sleep duration of 5.458 hours. Despite the majority having below the recommended 7 hours of sleep per night, the study found a weak negative correlation (-0.088) between sleep duration and academic performance (GPA). However, the p-value of 0.684 suggested that this correlation was not statistically significant. Discussion highlighted the importance of sleep for cognitive functions and academic success. Although the study contradicted some existing theories, it emphasized the need for further research with larger samples and more specific performance measurements. The findings could guide educational institutions in developing evidence-based interventions to improve students' sleep quality and, potentially, academic performance. this research contributes to the understanding of the complex relationship between sleep and academic achievement, prompting further exploration for a more comprehensive perspective.